Economic linkages inferred from news stories and the predictability of stock returns - Anna Scherbina; Bernd Schlusche (American Enterprise Institute (AEI), 2016)
We show that news stories contain information about economic linkages between firms and document that information diffuses slowly across linked stocks. Specifically, we identify linked stocks from co-mentions in news stories and find that linked stocks cross-predict one another's returns in the future. Our results indicate that information can flow from smaller to larger stocks and across industries. Content analysis of common news stories reveals many types of firm linkages that have not been previously studied. We find that the cross-predictability in returns remains even after firm pairs with customer-supplier ties are removed. Results show that both limited attention and slow processing of complex information contribute to slow information diffusion.
Keywords: A; 330; Stock market